HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN DIET PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Mailani, Fitri; Andriani, Rika Fitri (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
Diet on chronic renal failure patient is very important to avoid the appearance of uremia effect, liquid hoarding which can affect heart congestive failure and heart edema so that the death is last final. Family support is a factor that influences obedience. The aim of this research was to know the correlation of family support with diet obedience on chronic renal failure patient in Dr. ReksodiwiryoTk III hospitalPadang on year 2017. This research used descriptive analytic with the research design was cross sectional study. This research had been done on October 2016 to Mei 2017. The population in this research was 161 people and the sample was taken by accidental sampling in two weeks for 62 respondents at Hemodialisa room in Dr. ReksodiwiryoTk III hospitalPadang. The data analysis was done by computerization and analyzed in univariat with frequency distribution and bivariat used chi-square test with p value <0,05. The result of this research showed that more than a half respondent (62,9%) had high disobedience and more than a half respondent (61,3%) got less family support. Based on the statistic test, it showed that there was a useful relationship between family support and diet obedience (p= 0,003). To increase family support on diet obedience, it is suggested to medic and family to give the information, attention, and support to patient in doing diet therapy.Â Â